INTERNALISASAI NILAI TOLERANSI MELALUI PEMBELAJARAN BAHASA ARAB DI FAKULTAS TARBIYAH IAIN MATARAM - Arifin, Syamsul (JURNAL PENELITIAN KEISLAMAN, 2014)
A pheneomenon of the emergence of conflict within the society confirms the importance of tolerance as the basic values to build and strengthen social cohesivness. In this study, qualitative research approach is applied in order to obtain data about a process of internalizing tlorence values through arabic learning in faculty of Trabiyah IAIN Mataram. Based on this research, theoretical values internalizing in every subjects, especially arabic is a relativeness. However, such relativeness will decrease and become smaller corresponding with perception of subjects upon which the treatment is conducted. It happened due to some serious predicaments; the first is some of lectures do not have a right philosophy about the nature of the subjects, in which arabic is should be perceived withi which values education perspective should be incorporated; the second is not all of arabic lectures posess qualified skill in order to comprehend the pre-eminence of Arabic language in order to internalizing values of tollerance; the third is Quran which full of tolerance values and written in Arabic is not applied as the sources for learning arabic especially in ïºïºïºïºï» and Ø©Ø¡Ø§Ø±ï»; the fourth is arabic learning based on subject matter oriented cannot be avoided in cognitivistic learning system. Therefore some Arabic lectures do not have motivation and/or difficulties to explore values beyond all education elements.